Polygonatum daminense (Asparagaceae), a new species from China based on morphological and molecular evidence - Yang, Haijun; Wu, Baohuan; Chen, Zilin; Wang, Pan; Shi, Shi; Li, Feifei; Xu, Han; Cui, Dafang (Phytotaxa, 2020)
A new species of Polygonatum (Asparagaceae), P. daminense is described and illustrated from Pan’an, Zhejiang, China. The new species is similar to P. filipes, but differs from it for some features of the rhizome, the inflorescence, the peduncle, the pedicel, the bract, the bractlet and the perianth. The new species is only known from Zhejiang Province and is assessed as Data Deficient (DD).